17p13.3 microduplications are associated with split-hand/foot malformation and long-bone deficiency (SHFLD) - Armour, Christine M (Nature Publishing Group, 2011)
Split-hand/foot malformation with long-bone deficiency (SHFLD) is a relatively rare autosomal-dominant skeletal disorder, characterized by variable expressivity and incomplete penetrance. Although several chromosomal loci for SHFLD have been identified, the molecular basis and pathogenesis of most SHFLD cases are unknown. In this study we describe three unrelated kindreds, in which SHFLD segregated with distinct but overlapping duplications in 17p13.3, a region previously linked to SHFLD. In a large three-generation family, the disorder was found to segregate with a 254 kb microduplication; a second microduplication of 527 kb was identified in an affected female and her unaffected mother, and a 430 kb microduplication versus microtriplication was identified in three affected members of a multi-generational family. These findings, along with previously published data, suggest that one locus responsible for this form of SHFLD is located within a 173 kb overlapping critical region, and that the copy gains are incompletely penetrant.